2011
DOI: 10.4081/reumatismo.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid induced TNFR-related protein (GITR) as marker of human regulatory T cells: expansion of the GITR+CD25- cell subset in patients with systemic lupus erythematosus

Abstract: Objectives: Regulatory T cells (TREG) represent a T cell subset able to modulate immune response by suppressing autoreactive T-lymphocytes. The evidence of a reduced number and an impaired function of this cell population in autoimmune/ inflammatory chronic diseases led to the hypothesis of its involvement in the pathogenesis of these disorders. Glucocorticoid-induced TNFR-related protein (GITR) is a well known marker of murine TREG cells, but little is known in humans. The aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Another important Treg and activated T-cell marker is GITR (9,23) which correlates with CD25 expression. Recently, a novel CD4 Treg population was described and characterized, which is CD25 IowGITR+ CD127+ and exerts suppressor activity (16,20). We used CD25, GITR and CD 127 to analyze CD4 T-cell subsets (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important Treg and activated T-cell marker is GITR (9,23) which correlates with CD25 expression. Recently, a novel CD4 Treg population was described and characterized, which is CD25 IowGITR+ CD127+ and exerts suppressor activity (16,20). We used CD25, GITR and CD 127 to analyze CD4 T-cell subsets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GITR+population is distributed in the R1Treg region , but also in the R2 region. GITR+ cells inside gate R2 are CD25 IowGITR +CD127+ cells and can be considered a subset ofTreg cells according to the latest development in Treg subpopulations (16,20). Therefore, we evaluated the number of GITR+ cells inside gate R2 in tumor-positive and tumor-negative lymph nodes and found that also CD25 IowGITR +CD127+ cells are dramatically increased in tumor-positive lymph nodes (Fig.…”
Section: Analy Sis Ofthe Cd4+treg Populationmentioning
confidence: 99%
See 1 more Smart Citation